The Odyssey of Internment Objects: Material Culture and Unarticulated Family Trauma - Clarke, Angela (Italian Canadiana, 2024)
This article explores the significance of eight wooden internment objects created in the Kananaskis prisoner of war camp (c. 1940–1943) and their placement after the owner/creator returned from the camp. Through an analysis of the placement of these objects in a suitcase in a dark basement corner for over forty years, the researcher can ascertain the presence of unexpressed trauma. This article reveals an inherent ambivalence felt by the creator/owner with respect to the significance of these objects. On one hand, the owner – Federico Ghislieri – wanted to forget this period of internment, as indicated by his silence, yet, surprisingly, he could not dispose of the material vestiges of his camp experience. Instead, he negotiated this by preserving them yet hiding them from view. This article reflects on this contradiction through an analysis of the work of four psychological and material cultural theorists whose work provides a framework for comprehension: Jung, Bachelard, Veyne, and Greenblatt. Together, these thinkers suggest that the placement, and displacement, of household objects demarcate an object’s perceived value, both personally and in our culture. Finally, one can gain insight into how object placement can also be a political statement, reflecting long-held anxieties about an immigrant’s safety in the new country he calls home.